Effects of epibrassinolide on growth, physiological and biochemical responses and quality of rockmelon (Cucumis melo L. var. cantalupensis) cultivated under high temperature - Amarasinghe, Rathnayake Mudiyanselage Nilusha Thushari (2022)
Rockmelon (Cucumis melo L. var. cantaloupes) is a high-value crop and more suitable to be grown under protected environmental conditions. High-temperature stress reduces the profit for the farmers due to low yield, poor fruit quality, final yield loss depends on the plant growth stage, degree of temperature variation, and crop variety. Plant growth regulators like 24-Epibrassinolide (EBR) can regulate the cellular and physiological processes of plants and respond to high-temperature stress conditions. Hence, the general aim of this study was to study the effects of EBR on growth, physiological and biochemical responses, and fruit quality of rockmelon cultivated under high-temperature (HT) stress. In Chapter 4, a specific objective was to evaluate the growth, physiochemical, yield, and quality of different rockmelon cultivars grown under HT stress and to determine the most tolerant rockmelon cultivar to HT stress. The experiment was arranged in a nested design. Nested factor for cultivars (Lady-gold, Lady-green, Himalai-99, and Glamour), and temperatures (42±3°C as control and 47±3°C as 5°C higher than the control) and were replicated for four times. Growth traits including dry weight, relative growth rate, and leaf area (LA), were reduced in the vegetative and fruit development stages but increased in the flowering stage. Photosynthesis rate (PN), stomatal conductance (GS), transpiration rate (E), and chlorophyll content (Chl) were reduced in HT at three growth stages (vegetative, reproduction and maturity). Intercellular carbon dioxide concentration (Ci), and malondialdehyde (MDA) content were lowest in Himalai-99 and Glamour. HT stress significantly affects the fruit position in the main branch. When the temperature was high, the rockmelon fruits were most successfully formed at the upper branches part. In HT, Himalai-99 recorded a 7.7% higher fresh weight (FW) than in the AT. But in the other three cultivars, FW was significantly reduced. Fruit fresh weight was reduced at HT. In terms of tolerance level, Himalai-99 was the most tolerant cultivar, while Lady-green and Glamour were medium tolerant. Comparatively, Lady-gold was observed as the most heat-sensitive cultivar with the lowest yield. In Chapter 5, a study was conducted to study the plant physiological and biochemical responses to EBR of rockmelon under HT stress and to optimize the most productive concentration of EBR alleviating the high-temperature stress. The experiment was arranged in factorial (cultivar × [EBR]) and Randomized Complete Block Design (RCBD) with four replications. Fifteen days after transplant (DAP) seedling from cultivar Himalai-99 and Glamour was used and grown under 47±3°C protected greenhouse. The plants were subjected to different concentrations of EBR (0, 0.1, 0.2, 0.3 mg L-1). Chlorophyll content, PN, GS, E, Ci, MDA, proline content, electrolyte leakage (EL), peroxidase (POD) and catalase (CAT) activity, fruit position, fruit yield, total soluble solids (TSS) content, fruit firmness had a significant effect by different application of [EBR]. The application of 0.1 - 0.2 mg L-1 of EBR gave significant results to reduce the impacts of HT stress due to temperature under a protected greenhouse. Application of higher [EBR]s (0.3 mg L-1) decreased physiological and biochemical characteristics. Furthermore, EBR application enhanced the early fruiting of rockmelon; the lowest fruiting node number Himalai-99 was recorded at 0.1 mg L-1 and it was a 38% reduction. For Glamour variety, the lowest node number was recorded at 0.2 mg L-1and it was a 64% reduction from the control. In Chapter 6, the experiment was conducted in two stages to examine plant physiochemical behaviors towards frequency application of EBR under HT stress conditions and to study the effect of preharvest foliar application of EBR on postharvest quality of rockmelon fruit. The experiment was conducted under a 47±3ºC protected house and arranged in factorial (cultivars × EBR frequencies), and grown in RCBD with 4 replications. Two rockmelon cultivars (Glamour and Himalai-99) and four frequencies at 15 days interval (DI) and labeled as F1 (0 DAT), F2 (15 DAT), F3 (15+30 DAT), F4 (15+30+45 DAT) of 0.1 mg L-1 EBR were applied. Data on plant growth, physiology, and biochemical, other than yield and fruit quality parameters, was recorded at interval 7 DAT. In the second stage, the fruits obtained from first stage were kept under two temperature regimes where the fruits were stored in a cool room (CT) at 9ºC and ambient room temperature (RT) at 26ºC. Data on fruit weight loss, ethylene (C2H4) emission, TSS, ascorbic acid content, and antioxidant capacity was recorded at 5 and 10 days after harvest (DAH) for fruits stored in RT and 5, 10, 15, and 20 DAH for fruits stored at CT. Final values of plant dry weight, SLA, stomatal width, trichome density, average root diameter, root surface area, E, and POD had a significant effect from EBR frequency application and not recorded a significant difference between the two cultivars. Final values of LA, stomatal length, root length, PN, GS, Ci, chlorophyll content, chlorophyll fluorescence, proline content, MDA, and CAT were recorded with significant effects by EBR frequency and significant differences between the two cultivars. Preharvest application of EBR significantly affected fruit weight at harvest and weight loss, C2H4 emission, TSS, ascorbic acid content, and antioxidant capacity of stored fruits in CT and RT. The shelf life of rockmelon fruits was 10 and 20 DAH and in RT and CT, respectively. The application of EBR at F3 was showing the best growth performances and fruit quality. Application of 0.1 mg L-1 EBR at 15 DI increases the plant tolerance level in HT stress. The best performance in plant growth, physiology, biochemical, yield, and fruit quality was achieved when applying 0.1 mg L-1 EBR at vegetative (F2) and flowering (F3) stages. Application of EBR at the fruit development stage (45 DAP), improved plant performances but downregulated the fruit quality by delaying the fruit maturity. In conclusion, it was recommended that EBR can be used to mitigate the issues of HT stress related to the economical yield of rockmelon cultivars for future crop modification and breeding.